UV-Spectrophotometric Estimation of Venlafaxine Hydrochloride - SHARMA, RADHA; JAIN, SUMAN (Asian Journal of Chemistry, 2010)
A simple, accurate and convenient UV-spectrophotometric method has been developed for the determination of venlafaxine hydrochloride as pure and in its pharmaceutical formulations. In the proposed method venlafaxine hydrochloride showed maximum absorbance at 226 nm in acetonitrile and water in a ratio of 20:80. The method followed Beer's Lambert law in the concentration range of 2-20 μg/mL.